2018
DOI: 10.1016/j.ijbiomac.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a novel extracellular serine-protease with collagenolytic activity from Aspergillus tamarii URM4634

Abstract: An extracellular serine-protease from Aspergillus tamarii URM4634 was purified and characterized. The possibility of using Aspergillus tamarii URM4634 protease in detergent formulations and collagenolytic activity was investigated. The protease demonstrated excellent stability at pH range 7.0-11.0, the optimum being at pH 9.0. The enzyme was stable at 40 °C for 180 min, enhanced by Mg and Ca, but inhibited by Zn, and strongly inhibited by phenylmethylsulfonyl fluoride (PMSF), suggested as serine-protease. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 35 publications
2
8
0
1
Order By: Relevance
“…This enzyme is totally activated by Ca 2+ , Mg 2+ , and Fe 2+ , however, strongly inhibited by Cd 2+ , Ni 2+ , and Hg 2+ (2 mM). This is similar to other serine proteases such as ES1 [25], SAPB [32], serine protease isolated from Pleurotus sajor-caju increased by Ca 2+ and Mg 2+ [39], protease isolated from Aspergillus oryzae strain CH93 and protease isolated from Aspergillus tamari strain URM 4634 [47]. Serine proteases are used to incorporate two calcium binding sites [34, 48] and their addition increase thermostability.…”
Section: Discussionsupporting
confidence: 55%
“…This enzyme is totally activated by Ca 2+ , Mg 2+ , and Fe 2+ , however, strongly inhibited by Cd 2+ , Ni 2+ , and Hg 2+ (2 mM). This is similar to other serine proteases such as ES1 [25], SAPB [32], serine protease isolated from Pleurotus sajor-caju increased by Ca 2+ and Mg 2+ [39], protease isolated from Aspergillus oryzae strain CH93 and protease isolated from Aspergillus tamari strain URM 4634 [47]. Serine proteases are used to incorporate two calcium binding sites [34, 48] and their addition increase thermostability.…”
Section: Discussionsupporting
confidence: 55%
“…The same authors found that at 50°C for 30 min residual activity was strongly inhibited and maintained only 40.3% of its activity, resultswhich contrasted with the present investigation that at 50°C for 30 min it maintained residual activity at 86.99%. Silva et al, (2018) [9] purifying and characterizing a serine protease obtained from Aspergillus tamarii URM4634 by assessing the thermostability of the enzyme ranging from 20°C to 80°C for up to 180 min, concluded that the enzyme had stability of 20-40°C maintaining residual activity at more than 60%. Similar result to that observed in the present work, although the stability of the protease purified obtained residual activity higher than 70%.…”
Section: Stability In Temperature Differentmentioning
confidence: 99%
“…Aspergillus tamarii URM4634 is one strain of fungus isolated from Caatinga, a biome exclusive from Brazil [1], displayed the best performance concerning proteases production among thirty-four GRAS fungal strains [2]. Such a protease displayed collagenolytic and keratinolytic activities after purification, revealing the large applicability of this protease for industrial applications [3].…”
Section: Introductionmentioning
confidence: 99%
“…The solvated electron can react with a nearby disulfide bridge (RSSR) forming a disulfide electron adduct (RSSR •-)[37]. On other hand, photoionization of Trp residues may form an excited tryptophan that can undergo intersystem crossing, yielding a triplet state3 Trp, which may also lead to the disruption of a nearby disulfide bridge. Tyrosine residues may also undergo non-radiative decay, fluorescence decay, or undergo intersystem crossing to the triplet state ( 3 Tyr-OH).…”
mentioning
confidence: 99%